Competitive fitness of Pseudomonas aeruginosa isolates in human and murine precision-cut lung slices - Cramer, Nina; Nawrot, Marie Luise; Wege, Lion; Dorda, Marie; Sommer, Charline; Danov, Olga; Wronski, Sabine; Braun, Armin; Jonigk, Danny; Fischer, Sebastian; Munder, Antje; Tümmler, Burkhard (Frontiers in Cellular and Infection Microbiology, 2022)
Chronic respiratory infections with the gram-negative bacterium Pseudomonas aeruginosa are an important co-morbidity for the quality of life and prognosis of people with cystic fibrosis (CF). Such long-term colonization, sometimes lasting up to several decades, represents a unique opportunity to investigate pathogen adaptation processes to the host. Our studies aimed to resolve if and to what extent the bacterial adaptation to the CF airways influences the fitness of the pathogen to grow and to persist in the lungs. Marker-free competitive fitness experiments of serial P. aeruginosa isolates differentiated by strain-specific SNPs, were performed with murine and human precision cut lung slices (PCLS). Serial P. aeruginosa isolates were selected from six mild and six severe CF patient courses, respectively. MPCLS or hPCLS were inoculated with a mixture of equal numbers of the serial isolates of one course. The temporal change of the composition of the bacterial community during competitive growth was quantified by multi-marker amplicon sequencing. Both ex vivo models displayed a strong separation of fitness traits between mild and severe courses. Whereas the earlier isolates dominated the competition in the severe courses, intermediate and late isolates commonly won the competition in the mild courses. The status of the CF lung disease rather than the bacterial genotype drives the adaptation of P. aeruginosa during chronic CF lung infection. This implies that the disease status of the lung habitat governed the adaptation of P. aeruginosa more strongly than the underlying bacterial clone-type and its genetic repertoire.